2020
DOI: 10.1186/s13005-020-00222-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of intraoral scans in the mixed dentition: a prospective non-randomized comparative clinical trial

Abstract: Objective: In-vivo accuracy of intraoral scans of complete mixed dentitions of patients in active treatment have not yet been investigated. The aim was to test the hypothesis that dimensional differences between intraoral scans and conventional alginate impressions in the mixed dentition are clinically irrelevant. Methods: Trial design: Prospective non-randomized comparative clinical trial. Based on sample size calculation 44 evaluable mixed dentition jaws of patients in active orthodontic treatment were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Nowadays, the relative degree of accuracy between alginate impressions and the IOS method remains controversial. Liczmanski et al [16] reported that intraoral scans were more detailed and less error-prone compared to alginate impressions. On the other hand, Ender et al [10] reported that the accuracy of IOS and alginate impressions in a full arch model without orthodontic brackets were not different.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the relative degree of accuracy between alginate impressions and the IOS method remains controversial. Liczmanski et al [16] reported that intraoral scans were more detailed and less error-prone compared to alginate impressions. On the other hand, Ender et al [10] reported that the accuracy of IOS and alginate impressions in a full arch model without orthodontic brackets were not different.…”
Section: Introductionmentioning
confidence: 99%
“…2 Orthodontist, Department Orthodontics, University of Münster, Albert-Schweitzer-Campus 1, Gebäude W 30, D-48149 Münster, Germany. 3 Head of Department, Department of Cranio-Maxillofacial Surgery, University Hospital Münster, Albert-Schweitzer-Campus 1, Gebäude W 30, D-48149 Münster, Germany.…”
Section: Fundingmentioning
confidence: 99%
“…Intraoral scanners are of particular importance in surgery planning. Due to their high accuracy and practicability, they could replace impressions [3], as well as scattered dental morphology in cone-beam computed tomographs [4]. They are therefore applicable to create composite virtual skull models and conventional planning procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fewer triangular units result in a further generalized and vague representation of the surface. 14 , 15 , 16 A few 3-D inspection and mesh-processing software programs, 17 , 18 , 19 , 20 which offer tools and features for analyzing and optimizing digitized data before manufacturing, can be used to investigate the surface topography of digitized scans by displaying and measuring these triangular units and triangulation points.…”
Section: Introductionmentioning
confidence: 99%